Effects of a circular defect size and position on the damage progression in hybrid laminates under compressive loading. Issue 1 (21st October 2015) - Tala‐Ighil, Nacer; Mokhtari, Ahcene; Brick Chaouche, Amine
Abstract: The effects of a circular defect size and position on the post‐damage response of the FMLs laminates under compressive loading has been studied. Compression tests are performed on composite plates comprising a hole having different diameters (8 mm, 12 mm and 16 mm) and located at different positions (25%, 50% and 75%) in the loading direction. A numerical analysis using the finite element method FEM has permits the identification of the initiation zones and the description of the damage evolution in these laminates. The results of the numerical simulation are in good agreement with the experimental results. The FEM has well predicted the critical damage zones. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)